THE EFFECT OF PROVIDING CORE STABILITY EXERCISE ON INCREASING BALANCE IN THE ELDERLY - pratiwi, ika; Deasy Virka Sari; Addini, Ragil Aidil Fitriasari (STIKES Telogorejo Semarang, 2024)
Elderly people will experience decreased function in the neurological, sensory and musculoskeletal systems. In the sensory system, elderly people can experience visual, vestibular and proprioceptive disorders. Balance is a complex interaction originating from several systems including the sensory system (visual, vestibular, somatosensory and proprioceptive) and the musculoskeletal system. Core stability exercise is an exercise aimed at the core muscles, namely the abdominal and lumbopelvic muscles, where these muscles function as active stability in the core area (lumbopelvic-hip complex). Strong core muscles can improve balance and stability. With good stability, the center of gravity (COG) can be maintained above the base of support (BOS). OBJECTIVE: To determine the effect of providing core stability exercise on improving balance in the elderly. METHODS: Two group pre and post test design with control using a simple random sampling technique of 60 subjects. The measuring instrument used is the Timed Up and Go Test (TUGT). This research was conducted for 4 weeks. RESEARCH RESULTS: This study used non-parametric tests so that the difference test between initial and final balance values ​​in group I used Wilcoxon. The results of the initial and final balance difference test in group I obtained a value of p = 0.000, which means p < 0.05, so there is a significant difference in TUGT values ​​before and after being given core stability exercise. It can be concluded that core stability exercise has an effect on improving the balance of the elderly. CONCLUSION: Providing core stability exercises can improve balance in the elderly. Based on p value = 0.000 (p < 0.05)